Memory, anticipation, action – working with Troy D. Zars. (2nd January 2020) - Wolf, Reinhard; Heisenberg, Martin; Brembs, Björn; Waddell, Scott; Mishra, Aditi; Kehrer, Abigail; Simenson, Angelynn
Abstract: We present here our reflections on the scientific work of the late Troy D. Zars (1967 – 2018), on what it was like to work with him, and what it means to us. A common theme running through his work is that memory systems are not for replaying the past. Rather, they are forward-looking systems, providing whatever guidance past experience has to offer for anticipating the outcome of future actions. And in situations where no such guidance is available trying things out is the best option. Working with Troy was inspiring precisely because of the optimism inherent in this concept and that he himself embodied. Our reflections highlight what this means to us as his former mentors, colleagues, and mentees, respectively, and what it might mean for the future of neurogenetics.